Contribution to the Evaluation of Steel Structures Resistance to Lateral Displacement’s (International Journal of Innovative Research in Computer Science & Technology, 2017)
The choice of the global analysis method of  a steel structure is essentially related to its sensitivity to  second order effects. This sensitivity depends on the  structural strength to the lateral displacement’s. The  classification of structure as "flexible structure" or  "rigid structure" allows choosing the required method  of analysis for the latter. From a regulatory point of  view, a structure can be classified as rigid, if the ratio of  the value of elastic critical load for the instability into  the sway mode to the value of design vertical load is  greater than ten. In practice, the calculation of the  elastic total vertical load is not easy. For this reason,  studies have been made in this field and have  accomplished the proposal of simple expressions  computing as an alternative to the direct determination  of the critical elastic load of the structure. The main  objective of this work is to explore these alternative  methods in order to extend the study in this field and to  evaluate their robustness and the results of its  application on different types of structures.
Keywords: Buckling; Critical load; Global analysis method; Instability; Second order effects